Diversified Cropping System: Relay Intercropping of Lentils with Chickpeas [Morocco] - Devkota Wasti, Mina Kumari; Nangia, Vinay; Rekik, Fatma (WOCAT, 2022)
A Diversified Cropping System (DCS) results in a more resilient and productive cropping system. In this case, chickpeas were introduced as a relay intercrop between established lines of lentils. This not only had no negative effect on lentil yields, but also enabled the harvest of an extra crop: chickpeas.